THE USE OF PICTURE SERIES TO IMPROVE THE TENTH GRADERS’ SPEAKING ABILITY OF A RECOUNT TEXT (RETAIN, 2016)
THE USE OF PICTURE SERIES TO IMPROVE THE TENTH GRADERS’ SPEAKING ABILITY OF A RECOUNT TEXT Lidya R. Alfian English Education, Faculty of Languages and Arts, State University of Surabaya lidyaalfian@mhs.unesa.ac.id Abstract To be able to communicate in English, students need to improve their speaking skill. This research uses picture series for teaching speaking of a recount text. It uses one-group pre-test-post-test design, the population of which is the tenth grade students of SMAN 4 Surabaya, while the sample is X-IIS 2. This study aims to find out whether there is a significant difference in students’ speaking ability after being taught using picture series. The data are the scores of the students’ speaking in a pre-test and post-test and are analyzed using Paired samples T-test. The result shows that the mean scores of the post-test is better than that the pre-test. Furthermore, there is a significant improvement in terms of accent, vocabulary, grammar, fluency, and comprehension. Keywords: Speaking skill, picture series, recount text. Abstrak Untuk dapat berkomunikasi dalam bahasa inggris, siswa perlu menekankan kemampuan berbicara mereka. Penelitian ini menggunakan gambar berseri untuk mengajar berbicara dalam teks recount. Penelitian ini merupakan percobaan awal dengan menggunakan hasil pre-test dan post-test dari satu kelompok. Populasi dari penelitian ini siswa kelas X SMAN 4 Surabaya, sedangkan sampel menggunakan kelas X-IIS 2. Penelitian ini bertujuan untuk mencari tahu apakah ada perbedaan yang signifikan dalam kemampuan berbicara siswa setelah di ajarkan menggunakan gambar berseri. Data penelitian yang berkaitan dengan hasil hasil nilai pre-test dan post-test dan dianalisis dengan menggunakan sampel berpasangan T-test pada SPSS 16. Hasil penelitian ini menunjukkan bahwa nilai rata-rata dari post-test lebih baik dari pre-test. Terdapat kemajuan yang signifikan pada aksen, kosakata, tata bahasa, kefasihan, dan pemahaman. Kata kunci: Kemampuan berbicara, gambar berseri, teks recount.